2020
DOI: 10.3390/ijerph17082901
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed Surgical Training Model Based on Real Patient Situations for Dental Education

Abstract: Background: Most simulation models used at university dental clinics are typodonts. Usually, models show idealized eugnathic situations, which are rarely encountered in everyday practice. The aim of this study was to use 3D printing technology to manufacture individualized surgical training models for root tip resection (apicoectomy) on the basis of real patient data and to compare their suitability for dental education against a commercial typodont model. Methods: The training model was designed using CAD/CAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…Furthermore, more educational models of 3D printing in both the medical and dental fields have been developed and are becoming widely used effective learning tools for students when teaching and learning of anatomy, preoperative planning, technical skills, etc 15 . Modelling and simulation using 3D printing is also performed not only for planning surgeries on complex or unusual anatomical structures, but also for presurgical simulation practice 16–18 . Currently, several research has been undertaken to produce a model that reflects a more realistic clinical situation using 3D printing technology in the field of undergraduate dental education 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more educational models of 3D printing in both the medical and dental fields have been developed and are becoming widely used effective learning tools for students when teaching and learning of anatomy, preoperative planning, technical skills, etc 15 . Modelling and simulation using 3D printing is also performed not only for planning surgeries on complex or unusual anatomical structures, but also for presurgical simulation practice 16–18 . Currently, several research has been undertaken to produce a model that reflects a more realistic clinical situation using 3D printing technology in the field of undergraduate dental education 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Authors reported that it could be useful also in dental education, to teach for example endodontology [26]. A recent study also reported the use of 3D files based on real patient situation to teach dental surgery [27]. Moreover, these files can be easily integrated into preclinical simulation using haptic or virtual reality simulators, which is regarded with interest in dental education [7,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Future research needs to address the potential benefit of artificial intelligence for this part [24][25][26][27]. Once the G-code from CT data is deduced, the replica can easily be re-printed in a larger quantity, thereby opening the possibility for extended teaching and training purposes [28,29].…”
Section: Discussionmentioning
confidence: 99%